Evaluation of bacterial colonization on titanium dental implant surfaces following different instrumentation techniques: a comparative study - Ghaffar, Hareem (2025)
The use of various hygiene tools for implant maintenance affects surface configurations, which in turn affects bacterial adhesion on titanium implant surfaces, which can lead to peri-implant diseases. This study aimed to compare the surface topographies and Streptococcus sanguinis colonization on titanium implant fixture surfaces after polishing methods with Er, Cr: YSGG laser, airflow, and titanium brush group with control/untreated group using Scanning Electron Microscope (SEM) observation and Colony Forming Unit (CFU) counts. Twenty MegaGen titanium implant fixtures were randomly distributed into four groups. Five fixtures were randomly selected for the control/untreated (C) group while the other three groups were treated with Er, Cr: YSGG laser, airflow, and titanium brush. One fixture from each group was observed under SEM for surface topographies evaluation. All other samples were cultured with Streptococcus sanguinis for bacterial colonization and adhesion evaluation. One sample for each group was selected for SEM observation while the other samples were prepared for CFU counting. From the SEM analysis, the surface topography produced by the titanium brush showed a smooth surface followed by airflow with fewer surface irregularities, and the laser group showed a haphazard structure as compared to the control group. Similarly, for bacterial colonization, the titanium brush had the least bacterial cell growth, sparsely present on the surface same as the control group followed by the airflow group showed the multilayer chains of colonies, and the laser group showed the clusters of colonies. However, for the CFU result, statistical analysis revealed a significant value (p<0.05) among all four groups. Titanium brush was concluded as the least invasive and most effective instrumentation tool for implant fixture surface topographies and bacterial growth evaluated under SEM. However, from CFU counts, the airflow instrumentation was found to be the one having the least bacterial counts compared to other groups